Adaptive Automation for Intermittently Distracted UAV Pilots - Guri, Dominic. (Tufts University. Tisch Library., 2019)
New automation concepts are sought to support human pilots of remotely operated Unmanned Aerial Vehicles (UAVs) conducting observation missions where a pilot is subject to intermittent distractions, a term which we use to mean a frequent need to transition attention between controlling the UAV and accomplishing other mission-critical tasks, such as communicating or assimilating information from a secondary display. Our main contribution is to introduce a new human-oriented switching law designed for UAV steering human-oriented adaptive automation, with the intent of completing the observation task as quickly as possible during periods of intermittent distraction. This thesis presents two major contributions: (1) a new human-oriented switching law designed to smooth exchange of responsibility between the pilot and a deceleration-based backup automation, and (2) a control modality that allows the user to control the path or trajectory that a tracking controller can use to steer the UAV, so that the pilot can disengage from real-time control and attend to other tasks. Computer simulations are implemented to test the efficacy of the switching law and the backup automation as well as the new control modality. These simulations demonstrate that performance, as measured by task completion time, depends on context and can be tuned to improved performance. Both contributions are potentially useful in that they could be applied to support a pilot in controlling multiple UAVs.; Thesis (M.S.)--Tufts University, 2019.; Submitted to the Dept. of Mechanical Engineering.; Advisor: Jason Rife.; Committee: William Messner, and Christoph Borgers.; Keywords: Mechanical engineering, and Robotics.